Boswellia resin extract and propolis derived polyphenols in patients with type III chronic prostatitis/chronic pelvic pain syndrome: An Italian prospective multicenter study - Fabrizio Presicce; Francesco Barrese; Andrea Cantiani; Alessio Filianoti; Domenico Tuzzolo; Paolo Di Palma; Stefano Lauretti; Stefano Brunori; Marco Martini (Asian Journal of Urology)
Objective: To assess the efficacy and safety of a treatment regimen based on rectal administration of Boswellia resin extract and propolis derived polyphenols in patients with type IIIa and type IIIb chronic prostatitis and chronic pelvic pain syndrome (CP/CPPS). Methods: Patients with type IIIa and type IIIb CP/CPPS received one rectal suppository a day for 15 days per month for 3 consecutive months. Participants were evaluated with National Institutes of Health-Chronic Prostatitis Symptom Index (NIH-CPSI), the International Prostate Symptom Scores (IPSS), International Index of Erectile Function (IIEF), four-glass test, uroflowmetry, and prostate-specific antigen assessments at baseline and at Week 4, and Week 12. Primary endpoints were improvement in pain domain of NIH-CPSI and improvement of NIH-CPSI total score. Secondary outcomes included improvement of micturition and quality of life (QoL) domains of NIH-CPSI questionnaire. Results: A total of 61 males were enrolled. No adverse events were reported. Significant improvements from baseline to Day 30 were reported for NIH-CPSI total score (mean difference: −9.2; p<0.01), NIH-CPSI pain domain (mean difference: −5.5; p<0.01), NIH-CPSI micturition domain, NIH-CPSI QoL domain, and IPSS total score (mean difference: −5.6; p<0.01). No significant changes from baseline in terms of IIEF score or maximum flow rate were observed. At final follow-up (Day 90), further significant improvements in terms of NIH-CPSI total score (mean difference: −12.2; p<0.01), NIH-CPSI pain domain (mean difference: −6.6; p<0.01), NIH-CPSI micturition domain, NIH-CPSI QoL domain, and IPSS total score were reported. Conclusion: Rectal administration of Boswellia resin extract and propolis derived polyphenols is well tolerated and delivers a significant symptomatic improvement in most patients with type IIIa and type IIIb CP/CPPS.